ANALISIS UJI KELAYAKAN BUDIDAYA JAMBU BIJI KRISTAL (Psidium guajava L) DI DESA CIWARINGIN KECAMATAN LEMAHABANG KABUPATEN KARAWANG - Kundrat, Lily Sumarti, dan Umar Sumarna (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2022)
Crystal guava cultivation is widely developed in Ciwaringin Village, Lemahabang District, so that the development of crystal guava is in great demand by farmers, this development aims to meet market demand for crystal guava which is quite high with low supply from farmers and other reasons that are the basis is a pretty good market opportunity because it has been able to enter big markets in urban areas. Minim of information for farmers related to the research conducted in Ciwaringin Village is one of the factors for the lack of information for the development of crystal guava cultivation, thus making researchers want to analyze how technical and financial feasibility is on crystal guava farming in Ciwaringin Village, Lemahabang District, Karawang Regency.The business feasibility analysis carried out on crystal guava cultivation is the financial feasibility aspect includes the calculation of NPV, Gross B/C, Net B/C, IRR, Profitability Ratio, and the calculation of the length of the payback period (Payback Period), with the results of the NPV study of Rp.770.335.968, Gross B/C = 1.41, Net B/C = 2.27, IRR = 47,13%, PR = 1.27, and the rate of return on investment business investment PP (Payback Period) for 2.3 years, based on the results of the analysis, the cultivation of crystal guava in Ciwaringin Village, Lemahabang District, Karawang Regency can be said to be feasible